Place of the cardiosplenic axis in the development of fatal myocardial infarction - M. A. Kercheva; V. V. Ryabov; A. Е. Gombozhapova; A. A. Trusov; I. V. Stepanov; Yu. G. Kzhyshkowska (Российский кардиологический журнал, 2023)
Aim. To compare data on the features of spleen macrophage composition in patients with fatal myocardial infarction (MI) and in patients from the control group without cardiovascular disease (CVD).Material and methods. The study included patients with fatal MI (n=30) and control group (n=5) — persons without CVD who died from injuries not compatible with life. Macrophage infiltration of spleen and myocardium fragments taken during autopsy was assessed by immunohistochemistry using macrophage markers CD68, CD163, CD206, stabilin-1.Results. There were following number of cells studied by us in the red pulp (RP) in patients with MI: CD163+, 906 (661; 1101), CD68+, 898 (807; 1049), stabilin-1+, 811 (531; 966), CD206+, 11 (9; 19); control group: CD163+, 400 (315; 513), CD68+, 40 (37; 45), stabilin-1+, 186 (107; 206), CD206+, 80 (70; 84). The content of all cells in the RP in patients with MI was high and prevailed over their number in the control group, while only the CD206+ concentration was inferior in number; in the control group, CD163+ cells predominated (p<0,05). There were following number of cells in the white pulp (WP): CD68+, 312 (260; 348), stabilin-1+, 59 (40; 123), CD163+, 29 (17; 56), CD206+, 2 (1; 5) in the group with MI; CD68+, 3 (1; 4), stabilin-1+, 3 (2; 3), CD163+, 23 (1; 48), CD206+, 1 (1; 2) in the control group. In persons with MI, CD68+ cells dominated in WP, while in the control group — CD163+ (p<0,05). The minimum and comparable in WP in both groups was the number of CD206+ cells (p<0,05), which correlated in the control group with the level of stabilin-1+ and CD206+ cells (r=-0,9, p=0,003) and in patients with MI — with the level of CD206+ cells in the myocardium (r=0,6, p=0,004).Conclusion. The dominance of CD163+ cells in all functional spleen areas in the control group and CD68+ cells in patients with MI was revealed. The only cell type, the content of which in the control group prevailed over that in MI in RP and correlated in WP with its myocardial concentration, was CD206+.